Improving Equity in Remote Learning through Adaptive E-Learning Technologies for Multicultural and Multilingual Learners - Pasha, Lukita; Fitriani, Anandha; Hua, Chua Toh; Daeli, Mardaleni (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2025)
The rapid growth of remote learning has exposed significant inequalities in digital education access and learning outcomes, particularly for multicultural and multilingual learners. This study aims to explore how adaptive e-learning technologies can enhance equity in distance education by personalizing learning experiences and accommodating diverse linguistic and cultural backgrounds. A mixed-methods approach was used, involving surveys and interviews with students and teachers from three multicultural secondary schools in Indonesia. Quantitative data were collected through pre- and post-tests measuring learning engagement and comprehension, while qualitative insights were obtained through focus group discussions. The results indicate a significant improvement, with average pre-test scores of 65.3 increasing to 78.9 in the post-test (p < 0.05). Student engagement also rose, as weekly study time increased from 5.2 to 6.5 hours and completed modules improved by 30%. The adaptive technologies evaluated include multilingual user interfaces, culturally responsive learning content, and real-time feedback systems. The findings show a notable in crease in student motivation, participation, and academic performance among marginalized learner groups. Additionally, students reported a greater sense of inclusion and relevance in their digital learning environments. The study concludes that adaptive e-learning technologies can significantly reduce educational disparities when combined with inclusive instructional design. It recommends the integration of localized content and supportive policies to sustain equitable digital education for all learners, particularly in culturally diverse settings.